Estudo do desempenho e da comunidade microbiana de biorreatores tratando efluente anaeróbio contendo sulfeto - Graziella Patrício Pereira Garcia (2014)
The study proposal was treating UASB reactor effluent in two reactors, aiming to promote the biological oxidation of dissolved sulfide to elemental sulfur. The reactors were operated for seventeen months and the operating conditions were tested three hydraulic retention times, 24h, 12h and 6h, respectively, and two types of media materials, plastic rings and biobob. The results showed higher efficiency of sulfide removal in both reactors when operated with HRT of 12h, whose average efficiency was 90%. Moreover, the results showed that the formation of elemental sulfur from oxidation of sulfide occurred in two reactors operating at different conditions tested, and specifically in HRT of 24 hours, the reactor containing support media showed higher sulfur concentrations in effluent, biofilm and sludge as compared with the reactor containing biobob and without supporting material. As regards the presence of bacteria involved in the biological oxidation of sulphide in the two reactors, the purple and green sulfur bacteria were detected both by DGGE technique as by pyrosequencing-454 and the results from optical microscopy showed the predominance of similar purple colonies sulfur bacteria Chromatium sp. The pyrosequencing results showed that the reactor 1 (with plastic ring) operated at 24 and 12 hours HRT higher relative abundance of sulfur bacteria compared to reactor 2. This reactor in turn, provided without supporting material and the HRT of 12h showed the highest number of non-sulfur bacteria. Therefore, the plastic support ring provided further development of sulfur bacteria, when compared with the reactor without support and with biobob. Moreover, the best operating condition for promoting the recovery of elemental sulfur was observed in the HRT of R1 24h with plastic rings. This work showed that the configuration of the reactors, designed with a shape that resembles the settler compartment of an UASB reactor, can be used to promote the removal of dissolved sulfide effluent from anaerobic reactors treating sewage.